PERAN MANAJEMEN SUMBER DAYA MANUSIA UNTUK MENINGKATKAN KUALITAS LEMBAGA PENDIDIKAN ISLAM - Fitri, Anisa (ASCENT: Al-Bahjah Journal of Islamic Education Management, 2025)
Human Resource Management (HRM) plays a strategic role in improving the quality and sustainability of educational institutions, including Islamic educational institutions that possess distinctive values and goals. This study aims to analyze the role of human resource management in enhancing the quality of Islamic educational institutions, particularly through the professional, systematic, and sustainable management of educators and educational staff. This research employs a qualitative approach using a library research method. Data were collected from scholarly journal articles, academic books, and official documents related to human resource management and educational quality, and were analyzed using content analysis through data reduction, thematic presentation, and conclusion drawing. The findings indicate that HRM significantly contributes to improving the quality of Islamic educational institutions through human resource planning, competency-based recruitment, continuous professional development of teachers, academic supervision, and systematic performance evaluation. Furthermore, HRM plays an important role in strengthening teacher professionalism and internalizing Islamic values such as integrity, responsibility, and work ethics within the organizational culture of educational institutions. However, the implementation of HRM still faces challenges, particularly limited resources and the lack of standardized performance evaluation systems. Therefore, strengthening strategic and quality-oriented HRM is essential to achieving sustainable quality improvement in Islamic educational institutions.